2021
DOI: 10.1093/jac/dkaa556
|View full text |Cite
|
Sign up to set email alerts
|

What are the most effective community-based antimicrobial stewardship interventions in low- and middle-income countries? A narrative review

Abstract: Antimicrobial resistance (AMR) is a major global issue and antimicrobial stewardship is central to tackling its emergence. The burden of AMR disproportionately impacts low- and middle-income countries (LMICs), where capacity for surveillance and management of resistant pathogens is least developed. Poorly regulated antibiotic consumption in the community is a major driver of AMR, especially in LMICs, yet community-based interventions are neglected in stewardship research, which is often undertaken in high-inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…In people, the ability of ASGs to cause a decrease in AMU without adversely affecting patient outcome has been established in low-and middle-income countries as well as in hospital inpatient and outpatient settings in the USA [83][84][85]. Few studies have described the adherence to guidelines and/or the effect of guidelines on antimicrobial prescription habits among small-animal veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…In people, the ability of ASGs to cause a decrease in AMU without adversely affecting patient outcome has been established in low-and middle-income countries as well as in hospital inpatient and outpatient settings in the USA [83][84][85]. Few studies have described the adherence to guidelines and/or the effect of guidelines on antimicrobial prescription habits among small-animal veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…Future intervention efforts, therefore, need to be multifaceted to improve both antibiotic supply by health professionals and appropriate use by people. Although there are limited studies conducted in LMICs to evaluate educational interventions to improve appropriate antibiotic use in the community setting, a systematic review showed promising effects of multifaceted educational interventions in LMICs [53].…”
Section: Discussionmentioning
confidence: 99%
“…These tools can improve the knowledge translation from the guidelines to the physicians [ 40 ]. Interprofessional education, continuing professional development, or multifaceted, education-focused interventions are other proposals to improve adherence to recommendations [ 41 , 42 ]. A post-intervention analysis would then be appropriate to measure the effects of this intervention.…”
Section: Discussionmentioning
confidence: 99%